النمو والعمالة والفقر في البلدان النامية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لم تعد مشكلة الفقر محصورةً في أطر وطنية وجغرافية محددة بل أصبحت مشكلة ذات طابع واهتمام دولي بامتياز. فبعد أن انصبت الجهود المكثفة في القرن الماضي على كيفية تحقيق التنمية الاقتصادية والتنظير لها، فقد تبين حديثاً للاختصاصين أن هناك خللاً يعترض مسيرة التنمية، ويبطئ معدلات النمو الاقتصادي يتلخص ذلك السبب بمشكلة الفقر التي أصبحت عائقاً أساسياً لعملية التنمية. في هذا البحث تركزت الجهود على التعريف بمشكلة الفقر وترابطاته وطرق قياسه، والاستراتيجيات الوطنية والدولية لمكافحته وصولاً إلى وضع حلول قائمة على فرضيات وتصورات أولية قد تسهم في فهم أفضل لمشكلة الفقر ومعالجته ضمن إطار استراتيجية متكاملة ترتكز على عوامل ثلاثة هي تحقيق معدلات نمو اقتصادي مرتفعة أولاً والتوسع في إيجاد فرص العمل وتحقيق التشغيل الكامل ثانياً، وأخيراً تحسين الدخل ورفع مستوى المعيشة والحد من الفقر وتداعياته. The problem of poverty is no more confined to national and geographical frames. It has remarkably become a problem with international dimension and concern. After the intensive efforts which were concentrated, throughout the last century, on the methods of achieving economic development and on theorizing it, it recently became clear for specialists that there is a problem facing the process of development and halting the rates of economic growth. The cause of this problem can be summarized by the problem of poverty which became a major obstacle for development process. The efforts in this research were concentrated on defining the problem of poverty, its correlations, poverty measurement methods and national and international strategies for combating it. The goal is to establish solutions based on basic hypothesis and views which could contribute to a better understanding of the problem of poverty and curing it via a comprehensive strategy focusing on three factors: the first is achieving high economic growth rates; the second being the expansion of creating job opportunities and achieving full employment; and the third is improving the income and life levels and limiting poverty and its consequence.